(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2023)
We live in a time where writing is ever-present in our world. Communication often happens in the form of writing and the majority of jobs require the skill of writing. The problem at hand is that not everyone has equal access to formal writing. In the history of education, writing has been taught as a corrective process, in which some students are “called out” for writing and speaking improperly. Most often these students are those who speak a stereotyped language, such as African American Vernacular. The corrective method creates further roadblocks for students to grow in their writing. The solution to this problem is the teaching of code-switching, in which students learn to “flip” from the informal to the formal.